Domestic Violence against Women and Family Relationship Tarka Local Government of Benue State - Obademi Agnes Olufunke; Chiakyor Chiakyor; Joy Idowu (Pinisi Journal of Social Science, 2022)
The study assesses Domestic Violence against Women on Family Relationship in Benue State. Four research objectives were stated with four corresponding questions and null hypotheses. Domestic violence against women is domiciled in the home cutting across race, level of education since women are regarded as second class citizens. The study was conducted on married couples in Tarka Local Government area of Benue State, with a population of 40,515 using descriptive survey research design. The sample of 100 was selected using sample and sampling technique. The instrument used for collecting data for the study was a thirty-three (33) item questionnaire.  Data were collected by the researcher from the study area. Data collected were statistically analyzed using mean and standard deviation to obtain differences in responses of the subjects while Pearson Product Moment Correlation Coefficient was used to test the four null hypotheses at 0.05 level of significance. The findings revealed that there is a significant relationship between domestic violence against women and family relationship.  The first finding showed that, there was a high influence of spousal abuse against women and family relationship which stated that partners gave threatening looks when he/she did not agree with something said or done, which creates fear.  The researcher recommended that, Religious and elders in the community in Benue State should give talks on how good homes should be and how partners live peacefully by giving each other mutual respect and taking collective decision that concerns the family to strengthen family relationship. The researcher further recommended that Benue State Government should set up guidance and counseling centers on family matters, to educate partners on how best to improve family relationship.